Burden of human metapneumovirus infections among children with acute respiratory tract infections attending a Tertiary Care Hospital, Kathmandu - Jyoti Lamichhane; Milan Upreti; Krishus Nepal; Bishnu Prasad Upadhyay; Urusha Maharjan; Ram Krishna Shrestha; Ram Hari Chapagain; Megha Raj Banjara; Upendra Thapa Shrestha (BMC, 2023)
Abstract Background Acute respiratory infections (ARIs) are one of the most common causes of mortality and morbidity worldwide. Every year millions of children suffer from viral respiratory tract infections (RTIs) ranging from mild to severe illnesses. Human Metapneumovirus (HMPV) is among the most frequent viruses responsible for RTIs. However, HMPV infections and their severity among children have not been explored yet in Nepal. Purpose Therefore, the study was focused on HMPV infections and other potential viral etiologies or co-infections using multiplex PCR among children attending Kanti Children's Hospital and assessed the clinical characteristics of the infections as well as found the co-infections. A hospital-based cross-sectional study was designed and a convenience sampling method was used to enroll children of less than 15 years with flu-like symptoms from both outpatients and inpatients departments over three months of the study period. Results HMPV infection (13.3%) was the most predominant infection among the different viral infections in children with ARIs in Kanti Children's Hospital. The HMPV was more prevalent in the age group less than three years (21.8%). Cough and fever were the most common clinical features present in all children infected with HMPV followed by rhinorrhea, sore throat, and wheezing. HMPV-positive children were diagnosed with pneumonia (42.9%), bronchiolitis (28.5%), upper respiratory tract infections (14.3%), and asthma (14.3%). The prevalence of HMPV was high in late winter (14.3%) followed by early spring (13.5%). Conclusions This study provides the baseline information on HMPV and associated co-infection with other respiratory viruses for the differential diagnosis based on molecular methods and also the comparison of clinical presentations among the different respiratory syndromes.